A multidimensional assessment of nutritional and health status of rural elderly Malays - Shahar, Suzana; Ibrahim, Zuriati; Abdul Fatah, Afaf Ruhi; Abdul Rahman, Suriah; Mohd Yusoff, Noor Aini; Arshad, Fatimah; Yassin, Zaitun; Adznam, Siti Nur ‘Asyura (HEC Press, 2007)
A multidimensional assessment of nutritional and health status comprised of subjective global assessment (SGA), anthropometry function, biochemistry, dietary intake, social and health aspects was carried out on 820 older people (52.8% men and 47.2% women) from four rural areas of Peninsular Malaysia. A proportion of the subjects had been classified as either overweight (25.7%) or chronic energy deficient (20.3%). Although 49% of subjects had normal body weight, 68.4% have been classified as having mild to moderate malnutrition according to the SGA. Only 1.1% and 2.3% had low serum albumin and ferritin, respectively. Almost 80% of subjects, especially men, were at high risk of cardiovascular diseases on the basis of the assessment of total cholesterol and LDL-cholesterol. The majority of the subjects (87.2%) were fully independent in performing daily tasks, with men having a significantly higher score compared to women (p<0.001). However, men were less likely to be able to perform a flexibility test (50.7%) than were women (27.0%) (p<0.05). The mean energy intake for men (1412 +/- 461 kcal/d) and women (1201 +/- 392 kcal/d) were below the Recommended Nutrient Intake (RNI) for Malaysia, although this is a difficult assertion to make in an age-group which generally experiences declining energy expenditure. Moreover, 52.5% of men and 47.5% of women might have underreported their food intake. Dietary micronutrients most likely to be deficient were thiamin, riboflavin and calcium. It is concluded that a substantial proportion of rural elderly Malays had problems related to both undernutrition and overnutrition. An appropriate nutrition intervention program is needed to improve the nutritional status of rural elderly Malays.